Effectiveness of a peer-delivered, psychosocial intervention on maternal depression and child development at 3 years postnatal: a cluster randomised trial in Pakistan. (September 2020) - Maselko, Joanna; Sikander, Siham; Turner, Elizabeth L; Bates, Lisa M; Ahmad, Ikhlaq; Atif, Najia; Baranov, Victoria; Bhalotra, Sonia; Bibi, Amina; Bibi, Tayyaba; Bilal, Samina; Biroli, Pietro; et al.
Summary: Background: Maternal depression has a recurring course that can influence offspring outcomes. Evidence on how to treat maternal depression to improve longer-term maternal outcomes and reduce intergenerational transmission of psychopathology is scarce, particularly for task-shifted, low-intensity, and scalable psychosocial interventions. We evaluated the effects of a peer-delivered, psychosocial intervention on maternal depression and child development at 3 years postnatal. Methods: 40 village clusters in Pakistan were randomly allocated using a computerised randomisation sequence to receive a group-based, psychosocial intervention and enhanced usual care for 36 months, or enhanced usual care alone. Pregnant women (≥18 years) were screened for moderate or severe symptoms of depression (patient health questionnaire-9 [PHQ-9] score ≥10) and were recruited into the trial (570 participants), and a cohort without depression (PHQ-9 score <10) was also enrolled (584 participants). Including the non-depressed dyads enabled us to determine how much of the excess risk due to maternal depression exposure the intervention could mitigate. Research teams responsible for identifying, obtaining consent, and recruiting trial participants were blind to the allocation status throughout the duration of the study, and principal investigators, site coordinators, statisticians, and members of the trial steering committee were also blinded to the allocation status until the analysis of 6-month data for the intervention. Primary outcomes were maternal depression symptoms and remission (PHQ-9 score <10) and child socioemotional skills (strengths and difficulties questionnaire [SDQ-TD]) at 36-months postnatal. Analyses were by intention to treat. This trial is registered with ClinicalTrials.gov, NCT02658994 . Findings: From Oct 15, 2014 to Feb 25, 2016 46 village clusters were assessed for eligibility, of which 40 (including 1910 mothers were enrolled. After exclusions, 288 women were randomly assigned to the enhanced usual care group and 284 to the intervention group, and 1159 women were included in a group without prenatal depression. At 36-months postnatal, complete data were available from 889 mother-child dyads: 206 (72·5%) in the intervention group, 216 (75·3%) in the enhanced usual care group, and 467 (80·0%) women who did not have prenatal-depression. We did not observe significant outcome differences between the intervention group and the enhanced usual care group for the primary outcomes. The standardised mean difference of PHQ-9 total score was −0·13 (95% CI −0·33 to 0·07), relative risk of patient health questionnaire-9 remission was 1·00 (95% CI 0·88 to 1·14), and the SDQ-TD treatment estimate was −0·10 (95% CI −1·39 to 1·19). Interpretation: Reduced symptom severity and high remission rates were seen across both the intervention and enhanced usual care groups, possibly masking any effects of the intervention. A multi-year, psychosocial intervention can be task-shifted via peers but might be susceptible to reductions in fidelity and dosage over time (which were not among the outcomes of this trial). Early intervention efforts might need to rely on multiple models (eg, collaborative care), be of greater intensity, and potentially targeted at mothers who are at high risk for depression to reduce the intergenerational transmission of psychopathology from mothers to children. Funding: National Institutes of Health.